Get ready, get set, /spiːx/! Introducing a virtual reality interview simulator - Wan Noor Farah, Wan Shamsuddin; Nik Aloesnita, Nik Mohd Alwi; Umi Kalsom, Masrom (Universiti Kebangsaan Malaysia, 2024)
/spiːx/ is a virtual reality application that was inspired by the International Phonetic Alphabet (IPA) transcription of the word "speak" which aims to encourage more Malaysians to practice English communication. This virtual reality tool enables graduating students to refine their interview techniques before finishing their higher education, thereby boosting their employability and reducing their English-speaking anxiety. The study implemented experimental research design involving 94 students enrolled in a Professional English course. Results indicated that participants who underwent three virtual reality sessions with /spiːx/ experienced a reduction in interview anxiety almost double compared to their peers who did not. A paired samples t-test was performed, and result indicated a significance difference between the pre-test and post-test with the p-value <0.05. These findings demonstrate the application's effectiveness in alleviating interview stress among university students. Overall, the study underscores the considerable potential of virtual reality in enhancing education and communication skills.